2,3-Dibromo-3-phenyl-propionic acid. - Thong, Pui Yee; Lo, Kong Mun; Ng, Seik Weng (International Union of Crystallography, 2008)
In the crystal of the title compound, C(9)H(8)Br(2)O(2), inversion dimers linked by two O-H⋯O hydrogen bonds occur. All of the carbon and oxygen atoms are disordered over two sets of sites in a 2:1 ratio.